ERROR ANALYSIS ON THE STUDENTS WRITING OF COMPLAINING LETTER AT FIFTH SEMESTER OF ENGLISH LANGUAGE TEACHING DEPARTMENT Edulitics 2015 3 OF UNISDA LAMONGAN - Buyun Khulel (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2016)
ABSTRACT: This study presents the analysis of errors made by the students of fifth semester ofEnglish Language Teaching Department of UNISDA Lamongan in writing complaining letter basedon the surface structure. The researcher uses descriptive qualitative as the research design of thisstudy. In analyzing the data, the researcher follows some steps, they are: (1) coding the errors madeby the students, (2) classifying the errors the students made, (3) discussing and summarize thefindings. The researcher found that the level of grammatical accuracy in writing complaining letterwas 71%. Then, the level of grammatical inaccuracy in writing complaining letter was 29%. Thehighest level of error was omission (51 errors or 48%). The second level of error wasmisinformation (24 errors or 23%). The third level of error was addition (16 errors or 15%). The lastlevel of error was misordering (15 errors or 14%). Keywords: Error Analysis, Writing, Complaining Letter